English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

x^3-1
_____
x-1

divided by

x^2-1
_____
x+1

2006-11-24 14:56:17 · 4 answers · asked by Mark P 1 in Science & Mathematics Mathematics

4 answers

her's the solution in this link

2006-11-24 15:21:01 · answer #1 · answered by M. Abuhelwa 5 · 1 0

x^3 - 1 = (x - 1) (x^2 + x + 1)
x^2 - 1 = (x + 1) (x - 1)
So,
(x^3 - 1) / (x - 1) = x^2 + x + 1
(x^2 - 1) / (x + 1) = x - 1
Therefore,
((x^3 - 1) / (x - 1)) / ((x^2 - 1) / (x + 1)) = (x^2 + x + 1) / (x - 1)
which does not reduce any farther.

2006-11-24 15:08:49 · answer #2 · answered by bob the matrix 2 · 1 0

x^3-1 = (x-1)(x^2+x+1), so you can simplify the first fraction.

x^2-1 = (x+1)(x-1) so you can simplify the second fraction.

Then just write the first result over the second result and you have your answer. Any problems email h_chalker@yahoo.com.au

2006-11-24 15:04:24 · answer #3 · answered by Hy 7 · 0 1

x^3-1 = (x-1)(x^2+x+1)
so the first term is just (x^2+x+1)

x^2-1 = (x+1)(x-1)
so the second term is just (x-1)

The answer is (x^2+x+1)/(x-1)

2006-11-24 15:04:56 · answer #4 · answered by buaya123 3 · 1 0

fedest.com, questions and answers